Development and multi-use applications of dengue NS1 monoclonal antibody for early diagnosis. Issue 4 (12th January 2017) - Kathiresan, E.; Paramasivan, R.; Thenmozhi, V.; Das, Aparup; Dhananjeyan, K. J.; Sankar, S. Gowri; Jerald Leo, S. Victor; Rathnapraba, S.; Vennison, S. John
Abstract : Swift and early diagnosis of dengue is important for case management and epidemiological purpose. Abstract : Swift and early diagnosis of dengue is important for case management and epidemiological purpose. We developed a dengue NS1 antigen specific capture enzyme-linked immunosorbent assay (ELISA) for early diagnosis using a panel of monoclonal antibodies (mAbs), which are generated against monomeric non-structural (NS1) antigen expressed in E. coli . The mAbs were tested for its usefulness in dengue diagnosis during dengue outbreak in Tamil Nadu, India and compared with routinely used methods like RT-PCR, MAC-ELISA and commercially available NS1 antigen detection kit. The results of the comparative analysis suggest that the raised mAb may be used for the routine screening of suspected sera and also for the detection of dengue virus antigen in field collected vectors (mosquitoes).